Faster eating rates are associated with higher energy intakes during an ad libitum meal, higher BMI and greater adiposity among 4·5-year-old children: Results from the Growing Up in Singapore Towards Healthy Outcomes (GUSTO) cohort - Fogel, Anna (Cambridge University Press, 2017)
10.1017/S0007114517000848